2000
DOI: 10.1056/nejm200010123431502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Treatment with Inhaled Budesonide on Adult Height in Children with Asthma

Abstract: Children with asthma who have received long-term treatment with budesonide attain normal adult height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
230
3
22

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 517 publications
(260 citation statements)
references
References 35 publications
5
230
3
22
Order By: Relevance
“…Thus, final adult height is usually attained in association with the use of inhaled corticosteroids, as indicated by the results of 2 recently reported studies that investigated growth of children with asthma who were treated for many years with inhaled budesonide at doses of approximately 400 g/d. 16,17 In both studies, there was a reduction in growth velocity during the first year or so of budesonide treatment, followed by a recovery of growth velocity to a level similar to that in control groups. In the Agertoft and Pedersen 16 study, which followed up children until they reached adult height, children who used inhaled budesonide were as likely to reach their target adult height as their healthy siblings or children who had asthma and had not used inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, final adult height is usually attained in association with the use of inhaled corticosteroids, as indicated by the results of 2 recently reported studies that investigated growth of children with asthma who were treated for many years with inhaled budesonide at doses of approximately 400 g/d. 16,17 In both studies, there was a reduction in growth velocity during the first year or so of budesonide treatment, followed by a recovery of growth velocity to a level similar to that in control groups. In the Agertoft and Pedersen 16 study, which followed up children until they reached adult height, children who used inhaled budesonide were as likely to reach their target adult height as their healthy siblings or children who had asthma and had not used inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 88%
“…In school children, ICSs have been reported to affect shortterm growth (2 weeks), 9 intermediate-term growth (3-12 months), 10 -14 and long-term growth (4 -6 years), 15 although final adult height was not affected in 1 long-term observational study. 16 In children aged 2 to 8 years, intermediate-term growth of 12 months was reduced during daily treatment with 1 mg of nebulized budesonide (BUD). 17 Children who were 2 to 5 years of age and were treated for 24 weeks with FP (190 -565 g twice daily) also showed a significant decrease in height velocity compared with placebo, although at the end of treatment, height standard deviation scores did not differ significantly.…”
mentioning
confidence: 99%
“…A follow-up study of children over a 9.2-year period showed that they reached an appropriate final height. (2) In children, stature is a health indicator that is easy to obtain, is noninvasive and can be used to evaluate the efficiency and safety of the use of inhaled corticosteroids.…”
Section: Growth and Inhaled Corticosteroidsmentioning
confidence: 99%